Climate change and international migration: Evidence from Tajikistan - Enerelt Murakami (Asian Development Bank Institute (ADBI), 2020)
This paper investigates the impact of environmental factors that indicate climate change on household decisions to migrate abroad in the case of Tajikistan, an environmentally vulnerable and a labor-migrant source country in Central Asia. Both long-term climate variation (measured by weather anomalies) and short-term weather shocks (proxied by floods) are considered as environmental factors that could induce migration from Tajikistan. Using two waves of a nationally representative household survey and employing an empirical method within the New Economics of Labor Migration theory framework, the results highlight the differing effects of environmental factors (depending on their type and intensity) on the probability to migrate abroad. The findings show that a rise in air temperature from its long-term average reduces emigration, while changes in precipitation have a non-linear impact on emigration. There are substantial differences in seasonal weather anomalies, of which winter temperature and precipitation have the most significant impact on household decisions to migrate. Sudden onset environmental shocks appear to have a lagged impact on emigration.
Keywords: F22; O12; D10; C20; 330; migration; climate variation; environmental shock; Tajikistan